TECTONOGEOCHEMICAL AND BIOLOGICAL ASPECTS OF SALT LAKES ON THE TIBETAN PLATEAU - Zheng M.; Liu X.; Zhao W. (My University, 2007)
Based on saline minerals and geological settings, ordinary salt takes and special salt takes may be distinguished. The former occur in stable tectonic regions such as cratons and platforms; while the latter in tectonically active regions, including continental-margin back-arc basins or collision zones and basins at the rear of plate transform fault zones. Salt lakes of the Tibetan Plateau occur in a continent-continent collision zone. Boron and rare alkali elements mainly came from anatectic magma at the depth of the crust below the plateau, especially in the partial melting layer and recent anatectic magma in the Himalaya-south Qiangtang area, and hydrothermal water was the major carrier for transporting B and rare alkali elements from the depth to the salt lakes. Hydrochemical types and composition of the salt lakes constrain different minerogenetic specializations. An extensive investigation of 125 salt lakes in the northern Tibetan Plateau detected Artemia spp. in 30 lakes. In 21 lakes in the northern part of Qiangtang, 95 species of planktonic algae including Gloeothece linearis, Doctylococcopsis rhaphichoides Hansg, Chroococcus var. minor, Navicula sp., Cymbella pusilla, Dunaliella salina, Chlorella rulgaris and Diatoma elongagtum, and 16 species of planktonic animals, such as Voritilel a spp., Epistylis spp., Keratella quadrata, Daphnkiopsis tibetana and Artemia sp. were found.
Keywords: SALT LAKE; SALT LAKE BIOTA; TECTONO-GEOCHEMISTRY; TIBETAN PLATEAU